MEWASPADAI TITIK LEMAH PELAKSANAAN OTONOMI DAERAH - Waskito, Jati (Universitas Muhammdaiyah Surakarta, 2000)
The concept of region autonomy today is a demand of change that should be carried out immediately. However, still there are weak points that may occur from the carry out of the region autonomy policy. This identification is needed since the decision of the carry out of the policy of region autonomy is a fundamental change by the nation existence as its guarantee. This article tries to identify the probability of the various weak points of the region autonomy concept. As the first hypothesis, the writer suggests that there are still many